2012
DOI: 10.1080/13854046.2011.639314
|View full text |Cite
|
Sign up to set email alerts
|

Validation of MMPI-2-RF Validity Scales in Criterion Group Neuropsychological Samples

Abstract: This study utilized multiple criterion group neuropsychological samples to evaluate the "over-reporting" and "under-reporting" MMPI-2-RF validity scales. The five criterion groups included in this study were (1) litigating traumatic brain injury patients who failed Slick et al. criteria for probable malingering, (2) litigating traumatic brain injury patients who passed Slick et al. criteria, (3) mixed neuropsychological outpatients who passed SVTs and were diagnosed with primary neurological conditions, (4) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…We sought to add to the growing research literature on the association between MND and the over-reporting indicators of the MMPI-2-RF by utilizing a criterion groups design based on the well-validated Slick et al (1999) criteria. To date only two studies have utilized a criterion groups design when investigating the association between MMPI-2-RF over-reporting indicators and MND utilizing the Slick et al (1999) criteria (Schroeder et al, 2012;Wygant et al, 2011). Neither of these studies has investigated the utility of the MMPI-2-RF over-reporting scales in the prediction of MND among non-head injury disability claimants.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We sought to add to the growing research literature on the association between MND and the over-reporting indicators of the MMPI-2-RF by utilizing a criterion groups design based on the well-validated Slick et al (1999) criteria. To date only two studies have utilized a criterion groups design when investigating the association between MMPI-2-RF over-reporting indicators and MND utilizing the Slick et al (1999) criteria (Schroeder et al, 2012;Wygant et al, 2011). Neither of these studies has investigated the utility of the MMPI-2-RF over-reporting scales in the prediction of MND among non-head injury disability claimants.…”
Section: Introductionmentioning
confidence: 97%
“…However, in this study Rogers et al (2011) classified feigners based on below chance scoring on SVTs-a conservative approach leading to higher specificity, but much lower sensitivity than the more commonly used reliance on below cutoff scores on SVTs. Schroeder et al (2012) found that extreme scores on all of the MMPI-2-RF overreporting scales had excellent specificity and good sensitivity in differentiating litigating TBI patients classified as probable malingerers according to Slick et al (1999) criteria from those who were not classified as probable malingerers.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, they examined the combined use of the validity scales and found that the overall accuracy in identifying MND improved when multiple scales were employed. In a separate study employing TBI patients, Schroeder et al (2012) found that the MMPI-2-RF over-reporting scales exhibited excellent classification accuracy in discriminating TBI litigants classified as probable malingers from non-malingerers. Finally, Wygant et al (2011) found that Fs and FBS-r were good at identifying noncredible neurocognitive and somatic symptoms in a sample of litigants undergoing compensationseeking evaluations for disability who were classified with the MND and MPRD criteria.…”
Section: Mmpi-2-rf In Psychological Injury and Related Evaluationsmentioning
confidence: 97%
“…Due to the heterogeneous symptoms often presented during these evaluations, it is important to capture elements of feigning across all areas of functioning. The MMPI-2 and MMPI-2-RF have been more thoroughly examined in relation to the criteria for MND and MPRD (Bianchini et al, 2008;Greve et al, 2006;Schroeder et al, 2012;Tarescavage et al, 2013;Wygant et al, 2011). In comparison, the PAI has much fewer studies examining the relation between its validity indicators with cognitive PVTs, MND, and MPRD.…”
Section: General Conclusion Concerning the Assessment Of Response Bimentioning
confidence: 98%
“…Cases were excluded if validity indicators were significant but no mention was made of the VRIN and TRIN scales. Schroeder et al (2012) administered the MMPI-2 and MMPI-2-RF to two patients with frontotemporal dementia, two with early onset DAT, and one with AIDS-related dementia. Only valid profiles, based partly on VRIN-r and TRIN-r, were retained but the scores on these scales and the neuropsychological test data were not presented.…”
Section: Introductionmentioning
confidence: 99%